'Power base' tactics for workplace change – an interview study with industrial engineers and ergonomists. Issue 5 (4th May 2017) - Berlin, Cecilia; Neumann, W. Patrick; Theberge, Nancy; Örtengren, Roland
Abstract: The work activities of industrial engineers (IEs) and ergonomists drive workplace changes. The purpose of this study is to compare the work practices of the two professions and examine (1) how IEs and ergonomists gain influence over workplace changes and (2) whether there are prevailing types of intentional interaction behaviours called Power bases ( PB ) present in the interaction tactics they employ. The study identified key behavioural strategies used by the interviewees to successfully influence workplace changes; these were then mapped to their corresponding PB. Results showed that IEs and ergonomists were successfully influencing workplace changes using several tactics across the spectrum of PB, with the exception of Reward and Coercion . The study concludes with a list of recommended workplace change agent tactics, and proposes that a PB 'analytical lens' can serve to increase the budding ergonomists' critical and analytical skills when considering possible workplace change tactics. Practitioner Summary : This interview study examines how workplace ergonomics change agents, represented by the two professions: industrial engineers and ergonomists, perceive and exercise their capacity to influence workplace change. Key behavioural tactics that interviewees have found successful are reported, alongside effects on short- and long-term relations with other workplace-influencing stakeholders.